Efektivitas Kerjasama China dan Brazil: Studi Kasus Ketenagakerjaan Brazil di Belo Monte - Bernad, Katherina Nikita; Dewi, Elisabeth (Universitas Komputer Indonesia, 2024)
China, as a developed country, has established bilateral cooperation with Brazil through investment in the Belo Monte project. This journal article further discusses the effectiveness of the Belo Monte project, a collaboration between China and Brazil. Based on constructivist theory, this cooperation is not only based on the interests of both countries, but also involves the implementation of rules and norms that recognize issues such as violence, conflict, and racial issues. The assessment of the Belo Monte project, which follows the criteria of the World Bank Group covering aspects such as wages, work duration, contract clarity, workload, and worker safety, shows that the Belo Monte project has succeeded in managing the aspects provided by the World Bank Group. The Belo Monte project through constructivist theory is considered quite effective and is able to fulfill and protect the human rights of individuals involved in the project and is in line with the principles of constructivism applied in bilateral cooperation between China and Brazil. Keywords — Belo Monte, Brazil, China, cooperation, labor